Identification of cuproptosis-related subtypes, construction of a prognosis model, and tumor microenvironment landscape in gastric cancer - Wang, Jinyan; Qin, Dongmei; Tao, Zhonghua; Wang, Biyun; Xie, Yizhao; Wang, Ye; Li, Bin; Cao, Jianing; Qiao, Xiaosu; Zhong, Shanliang; Hu, Xichun (Frontiers in Immunology, 2022)
Cuproptosis is a novel identified regulated cell death (RCD), which is correlated with the development, treatment response and prognosis of cancer. However, the potential role of cuproptosis-related genes (CRGs) in the tumor microenvironment (TME) of gastric cancer (GC) remains unknown. We downloaded transcriptome profiling and clinical data of GC samples from the Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) database to describe the alterations of CRGs from genetic and transcriptional fields. We identified two cuproptosis molecular subtypes based on the expression profiles of CRGs and found that multi-layer CRGs alterations were significantly associated with clinical features, prognosis, metabolic related pathways and immune cell infiltration in TME. Then, differentially expressed genes (DEGs) were screened from distinct molecular subtypes and further analyzed by univariate Cox regression analysis to obtain prognosis related DEGs. Patients were again grouped into two gene subtypes, which were significantly associated with patients’ age, grade, T and N stage, and survival of patients, according to the expression profiles of prognostic DEGs. CRG Risk scoring system for survival prediction was further constructed and validated. Finally, we established a highly accurate nomogram for promoting the clinical applicability of the CRG Risk scoring system. A high CRG Risk score, characterized by decreased microsatellite instability-high (MSI-H), tumor mutation burden (TMB) and cancer stem cell (CSC) index, and high stromal and immune score in TME, indicated poor survival. Moreover, the CRG Risk score was greatly related with the sensitivity of multiple drugs. Our comprehensive analysis of CRGs in GC demonstrated their potential roles in TME, clinicopathological features, and prognosis. These findings may improve our understanding of CRGs in GC and provide new perceptions for doctors to predict prognosis and develop more effective and personalized therapy strategies.